PERIOPERATIVE REGISTERED NURSE EXCELLENCE RAISING THE BAR AT THE POINT OF CARE – STAR PERFORMANCE - Shewchuk, Muriel (Operating Room Nurses Association of Canada Journal, 2014)
The role of the professional Registered Nurse (RN) employed in the Surgical Suite/ Operating Room (OR), is one of the most misinterpreted, misunderstood, feared, complex, integrated, yet rewarding roles in the nursing field. Patients are at a vulnerable time, are depending on the outstanding knowledge, skill, critical thinking and advocacy of the RN within the team. There is simply no other place like it in health care. If your passion is to excel through continual learning, possess Type A critical thinking and response skills, have tolerance for stress related behaviours of others, stamina for “hard work”, are a leader, exhibit kindness and respect, providing continual teaching/mentoring, and thrive within a multidisciplinary team, Perioperative nursing can be the best life long career. The long list of attributes are essential, but also a very tall continuous order. If you are viewing the position as a “job” with weekends off, then it will be difficult to thrive in this career choice! There is a right place for everyone. Without the excellence of practice attributes embedded within the Perioperative RN, the OR can be a very difficult career choice, with potential long term and negative impact on the RN and teammates. The focus of this article is to define the expectation for excellence of practice, for all RN’s, working at the point of care for the scrub and circulating role.